The Application of Flash Media "Storyboard Chemistry" as an Interactive E-Module in Learning B3 Concepts at Queen Al-Falah High School - Mazraatun Naimah; Khusnul Khotimah; Wita Aliffina Fransiska Putri; Desiana Brilianti Nugraha; Nafilah Azizah; Farel Ramadani; Adji Indra Fergiansyah (Epistema, 2026)
This study seeks to evaluate the efficacy of the interactive e-module “Storyboard Chemistry” in enhancing students’ comprehension of Hazardous and Toxic Substances (B3) concepts at SMA Queen Al-Falah. The study utilized a quasiexperimental approach with a one-group pretest-posttest design, comprising 32 students. Data were gathered via pretest and posttest evaluations, along with student reaction surveys. The findings indicated a notable enhancement in students' academic performance, as the average score rose from 56.30 in the pretest to 83.40 in the posttest. Statistical investigation employing a paired sample t-test revealed a significant difference (p < 0.05), affirming that media utilization positively influenced students' conceptual comprehension. The N-Gain study indicated a moderate to substantial degree of enhancement. The students' reactions to the media were largely favorable, reflecting heightened motivation, engagement, and comprehension of the topic. The incorporation of visual components, animation, and narrative in the emodule effectively converted abstract chemistry principles into tangible and significant learning experiences. Consequently, "Storyboard Chemistry" is regarded as an excellent and unique educational tool that can improve the quality of chemical instruction. Keywords: e-module interaktif, storyboard chemistry, konsep B3, hasil belajar, teknologi pendidikan